Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1161/01.str.0000221815.64093.8c
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Aphasia Attributable to First Ischemic Stroke

Abstract: Background and Purpose-In a geographically defined population, we assessed incidence and determinants of aphasia attributable to first-ever ischemic stroke (FEIS). MethodsA 1-year prospective, population-based study among the permanent residents of the canton Basle City, Switzerland, was performed using multiple overlapping sources of information. Results-Among 188 015 inhabitants, 269 patients had FEIS, of whom 80 (30%; 95% CI, 24 to 36) had aphasia. The overall incidence rate of aphasia attributable to FEIS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
205
1
10

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 555 publications
(240 citation statements)
references
References 43 publications
(55 reference statements)
8
205
1
10
Order By: Relevance
“…Aphasia is a language disorder limiting the ability of up to one-third of stroke survivors to access, use, and understand words [2]. Co-morbid motor speech problems include apraxia of speech and dysarthria, causing difficulty speaking, poor voice quality, imprecise articulation, and reduced perception/production of speech prosody [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aphasia is a language disorder limiting the ability of up to one-third of stroke survivors to access, use, and understand words [2]. Co-morbid motor speech problems include apraxia of speech and dysarthria, causing difficulty speaking, poor voice quality, imprecise articulation, and reduced perception/production of speech prosody [3].…”
Section: Introductionmentioning
confidence: 99%
“…Speech language therapy programmes exist for people with PD [20] and stroke [21] but access to them is limited by high costs and limited availability of therapists [2,20]. While short-term speech language therapy after acute stroke is generally provided, long-term care for people with stroke or PD is not routine, resulting in many unmet needs [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…These patients are increasingly treated with thrombolysis. Retrospective studies showed that patients with mild stroke symptoms and low baseline NIHSS scores may benefit from thrombolysis with low complication rates [6,7]. On the other hand could it be shown that spontaneous recovery of aphasia as measured by NIHSS occurred in 74% of all and 90 % of patients with mild stroke symptoms after six months [8].…”
Section: Introductionmentioning
confidence: 99%
“…38 sujets de langue maternelle française, âgés de 48 ans et plus (en relation avec l'augmentation de l'incidence d'une attaque cérébrale en fonction de l'âge [8]) ont été testés. Les critères d'exclusion étaient: un trouble auditif ou visuel; une anesthésie générale dans les trois mois avant l'examen; une hospitalisation due à une maladie psychiatrique; un traumatisme cérébral ou une maladie neurologique; des maladies systémiques graves; des douleurs sous n'importe quelle forme.…”
Section: Sujetsunclassified